The Biostimulation Of Low Level Laser Irradiation On Blood Parameters: Ex Vivo - Al Musawi, Mustafa Salih Ali (2017)
Various low-level laser wavelengths have been used for a variety of clinical applications because of their ability to modulate blood rheology and improve microcirculation. The response of human blood to low-level laser irradiation (LLLI) provides important information about the interactions of laser light with living tissues. This study was designed to investigate whether in vitro LLLI changes the erythrocyte sedimentation rate (ESR) and other blood indices of whole blood. Blood samples were collected by venipuncture into ethylenediaminetetraacetic acid (EDTA)-containing tubes. Each sample was divided into two equal aliquots as a control (non-irradiated) and irradiated samples. The irradiated sample was subjected to LLLI doses of 36, 54, 72 and 90 J/cm2 at wavelengths of 405, 589 and 780 nm.